Small fiber pathology in fibromyalgia syndrome - Claudia Sommer; Nurcan Üçeyler (PAIN Reports)
Abstract. About 50% of women with fibromyalgia syndrome have reduced skin innervation. This finding is consistent in patient cohorts from different regions of the world. Small fiber function may also be affected, as shown by various studies using different methods, such as quantitative sensory testing or special small fiber neurophysiology such as C-fiber microneurography. Microneurography in particular has shown increased spontaneous activity, mechanosensitivity, and enhanced activity-induced slowing in C fibers of patients with fibromyalgia. Generalized reduction of skin innervation, ie, proximally and distally, was associated with higher symptom severity and more pronounced central nervous system changes as seen in magnetic resonance tomography. The question whether peripheral or central nervous system changes come first, or whether both are signs of an underlying pathology, has not been resolved yet. For clinical practice, it is important to note that reduced skin innervation in fibromyalgia must not be confused with small fiber neuropathy, which is a separate entity with different characteristics and pathophysiology. Further prospective research is warranted to transfer these findings in the peripheral nervous system into clinical fibromyalgia patient management.